The role of public policy in promoting gender equality in Malta: A diachronic approach - Cassar, Maria Francesca; Cutajar, JosAnn; Thake, Anne Marie (International Journal of Social Sciences Perspectives, 2023)
This article analyzes the major policy and regulatory framework of gender equality policies enacted in Malta between 1921-2021. A diachronic approach was adopted. A historical analysis of the development of gender equality policies was carried out by analyzing official documents. The data was consolidated with the findings which emerged from the twelve in-depth interviews held with key institutional actors. They were involved in the design and implementation of gender equality policies, procedures, and measures. Since Malta does not have an umbrella policy on gender equality, this is an important public policy field. Gender equality laws and policies have evolved over the years, often in a piecemeal manner, due to pressure from international bodies. Efforts have been made to eliminate gender discrimination in the public sector and service with the aim of establishing a standard for the private sector. Malta’s gender equality laws and policies have brought about change in some areas, but others need to be further developed. The Gender Equality Index devised by the European Institute for Gender Equality (EIGE) shows that Malta has improved in some domains but not in others.